PENGARUH KESEJAHTERAAN EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH MENENGAH KEJURUAN - Afzanul Firdaus; Junil Adri; Irzal Irzal; Eko Indrawan (Jurnal Vokasi Mekanika (VoMek), 2024)
This study explores the impact of parents' economic status on students' learning motivation at SMKN 1 Guguk. Education is the cornerstone of national development, and in Indonesia, educational success is determined not only by the quality of teaching but also by external factors such as parental economic status. The research reveals that family economic level plays a crucial role in students' access to educational facilities, which affects their learning motivation. Students from well-off families tend to have more learning tools and adequate support, whereas those from low-income families often lack essential facilities, impacting their motivation and academic performance. This study employs a descriptive method with a quantitative approach, involving 79 students as the sample. A questionnaire was used as the research instrument to measure the variables of parents' economic status and students' learning motivation. The analysis results show a significant correlation between economic conditions and students' learning motivation. These findings provide insights for educators, parents, and policymakers in designing effective strategies to enhance students' learning motivation, notably for those from economically disadvantaged families. The results are expected to improve the quality of education at SMKN 1 Guguk and serve as a basis for more inclusive and equitable educational policies in Indonesia.